Letter (copy) - Norman, F. H.
025a-0064-001 COPY. Abb. 7711 - N.A. Guttery Ministry of Shipping, Berkeley Square House, Berkeley Square, London, W.1. QM.490840 23rd. February, 1940. Dear Mr. Tennant, In reply to your letter of the 6th. February, about some Spanish Officers who would like to serve in the Merchant Navy, I should explain that so far as the Ministry of Shipping are concerned, there is no barrier to the employment of alien officers so long as the requirements of the Aliens Restriction (Amendment) Act 1919 and the Merchant Shipping Act are complied with, i.e. where the officer must hold one of our Certificates in order to serve in a certain capacity, these requirements must be adhered to. So far as other ranks of officers are concerned, the question is one primarily for the Departments responsible for security, i.e. the Home Office and the Admiralty who act together in this matter. If we are advised that they have no objection to the employment of a particular individual, then subject to what I have said above, we raise no objection. There is, however, as you doubtless know, a general requirement that aliens should not be employed in vessels used by Sea Transport Department for attendance on the Fleet and similar Service duties. Yours sincerely, (sgd) F. H. Norman. 292/946/25a/64